2011
DOI: 10.1038/aja.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of insulin-like growth factor-binding protein-3 is implicated in erectile dysfunction in two-kidney one-clip hypertensive rats after propranolol treatment

Abstract: This study aimed to investigate the role of insulin-like growth factor-binding protein-3 (IGFBP-3) in erectile dysfunction (ED) in two-kidney one-clip (2K-1C) hypertensive rats treated with the b-blocking agent propranolol. Adult male Wistar rats were randomly divided into three groups: a normal control group, a hypertensive control group and a propranolol treatment group (n59). After 4 weeks of propranolol treatment, intracavernous pressure (ICP) responses to electrical stimulation of the cavernous nerves wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We have observed the higher expression of mRNA and protein of IGFBP-3 in old rat penile tissues which is related ED [3]. The higher expressions of IGFBP-3 were also observed in corpus cavernosum tissues of DM rats [13] and hypertensive rats [14]. It showed that IGFBP-3 might play an vital role in the development of ED.…”
Section: Changes Of Nos Activity and Of Cgmp Concentrationmentioning
confidence: 66%
“…We have observed the higher expression of mRNA and protein of IGFBP-3 in old rat penile tissues which is related ED [3]. The higher expressions of IGFBP-3 were also observed in corpus cavernosum tissues of DM rats [13] and hypertensive rats [14]. It showed that IGFBP-3 might play an vital role in the development of ED.…”
Section: Changes Of Nos Activity and Of Cgmp Concentrationmentioning
confidence: 66%
“…We have observed the higher expression of mRNA and protein of IGFBP-3 in old rat penile tissues which is related ED [3]. The higher expressions of IGFBP-3 were also observed in corpus cavernosum tissues of DM rats [13] and hypertensive rats [14]. It showed that IGFBP-3 might play an vital role in the development of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Erectile function was evaluated by measuring intracavernous pressure (ICP) following electrostimulation of the cavernous nerves at 4 weeks of propranolol treatment as previously described (Zhou et al ., ). Then, all rats were sacrificed with an i.p.…”
Section: Methodsmentioning
confidence: 97%
“…Although a previous report suggested that the decreased IGF‐1 availability could be associated with the development of ED in two‐kidney one‐clip (2K‐1C) hypertensive rats (Zhou et al ., ), there are no many studies on elucidating a relation between the decrease of the IGF‐1 availability and spontaneously hypertensive ED. So here we employed spontaneously hypertensive rats as a model to investigate the role of IGF‐1 on hypertensive ED in this study.…”
Section: Introductionmentioning
confidence: 99%